An innovative approach to design SOFC air electrode materials: high entropy La1−xSrx(Co, Cr, Fe, Mn, Ni)O3−δ (x = 0, 0.1, 0.2, 0.3) perovskites synthesized by the sol–gel method. Issue 46 (1st October 2020) - Dąbrowa, Juliusz; Olszewska, Anna; Falkenstein, Andreas; Schwab, Christian; Szymczak, Maria; Zajusz, Marek; Moździerz, Maciej; Mikuła, Andrzej; Zielińska, Klaudia; Berent, Katarzyna; Czeppe, Tomasz; Martin, Manfred; et al.
Abstract : For the first time, the high entropy perovskites from La1− x Sr x (Co, Cr, Fe, Mn, Ni)O3− δ ( x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5) series are documented to possess attractive properties as a candidate air electrode material for Solid Oxide Fuel Cells (SOFCs). Abstract : Among the for the first time reported Cr-containing high entropy La1− x Sr x (Co, Cr, Fe, Mn, Ni)O3− δ ( x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5) perovskite-type oxides, the selected Sr-doped La0.7 Sr0.3 (Co, Cr, Fe, Mn, Ni)O3− δ material is documented to possess attractive properties as a candidate air electrode material for Solid Oxide Fuel Cells (SOFCs). Nanosized powders of the considered oxides are obtained using a modified Pechini sol–gel method. In the formed solid solution with a simple perovskite structure the strontium solubility limit is found to be at least x = 0.3. Room temperature (RT) structural data indicate the presence of rhombohedral structural distortion ( R 3̄ c symmetry) in the materials. High-temperature structural studies for the selected La0.7 Sr0.3 (Co, Cr, Fe, Mn, Ni)O3− δ indicate the occurrence of a phase transition to an aristotype Pm 3̄ m structure at ca. 800 °C. The linear thermal expansion coefficient in the RT-1000 °C range is found to be moderate, 16.0(3) × 10 −6 K −1 . The results of impedance spectroscopy measurements support the semiconducting-type behavior of the electrical conductivity for all single-phase materials, in a temperature range of RT-1000 °C. The maximum recorded conductivity for the La0.7 Sr0.3 (Co, Cr, Fe, Mn, Ni)O3− δ composition exceeds 16 S cm −1 in the 900–1000 °C range, being suitable for application. Furthermore, chemical stability toward the La0.8 Sr0.2 Ga0.8 Mg0.2 O3− δ (LSGM) electrolyte is proven. Considering the presence of chromium, typically deleterious to the performance, the measured value of the total cathodic polarization resistance for the La0.7 Sr0.3 (Co, Cr, Fe, Mn, Ni)O3− δ -based electrode, being 0.126 Ω cm −2 at 900 °C, seems to be very attractive. The results obtained for a button-type fuel cell indicate power densities at a level of 550 mW cm −2 at 900 °C. Therefore, it can be considered that the high entropy-based approach enables to propose alternative SOFC air electrode materials, with otherwise inaccessible chemical compositions.